Mutu Lulusan Program Prodistik MAN 2 Jember dalam Kesiapan Menghadapi Dunia Kerja - Mochammad Salman Alfarizi Wahyu Romadhani; Nur Ittihadatul Ummah (Yayasan Mutiara Hati Moeslem, 2025)
This study analyzes the quality of graduates from the PRODISTIK MAN 2 Jember Program in terms of their readiness to enter the workforce, including technical and soft skills competencies, contributions from practical training and internships, and the effectiveness of program evaluation. A descriptive qualitative approach was used with purposive informants from graduates, instructors, and administrators. Data were obtained through interviews, observations, and documentation, and analyzed using the Miles and Huberman model. The results show that graduates' technical competencies are adequate in graphic design, multimedia, and basic programming, but weak in networking and troubleshooting. Soft skills are in the good category. Practical training and internships have a positive impact, but are not yet evenly distributed and are not yet based on competency standards. Program evaluation has been carried out, but does not yet use measurable quality indicators and does not yet systematically involve industry. Overall, graduate quality is adequate, with variations in ability influenced by practical experience and the strength of program quality assurance.